Implementasi Teknologi Blockchain dalam Sistem Pemilu: Tinjauan Fikih dan Maqashid al-Syari'ah terhadap Transparansi dan Kepercayaan Publik - Muhammad Siraz; Wahyu Akbar; Muhammad Rani (Journal of Fiqh in Contemporary Financial Transactions, 2026)
This study aims to examine the compatibility of blockchain technology with the principles of fiqh al-siyasah and maqashid al-shariah. This study employs a combined approach: a descriptive qualitative method based on a literature review to analyze books, journals, and official KPU regulations, as well as a systems engineering approach to develop and test a Solidity-based smart contract deployed on the Polygon Amoy Testnet via the Remix IDE and integrated with MetaMask. The results show that the developed e-voting system successfully recorded 362 on-chain transactions, all of which were verified, and demonstrated that the key characteristics of blockchain decentralization, immutability, transparency, and smart contracts are inherently aligned with Sharia principles such as justice (‘adl), trustworthiness (amanah), and public interest (maslahah), and are thus aligned with the maqashid of Sharia in safeguarding religion, life, intellect, lineage, and property. Consequently, the application of blockchain in elections both theoretically and technically has the potential to strengthen public trust and create a more ethical system of governance in accordance with Islamic values.